2021
DOI: 10.1371/journal.pone.0259434
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the physician workforce: Specialty choice decisions during medical school

Abstract: Background Despite efforts to increase the overall diversity of the medical student body, some medical specialties have a less diverse applicant pool based on both gender and race than would be expected based on medical graduate demographics. Objectives To identify whether women and Underrepresented in Medicine (URiM) medical students have baseline differences in their career interests or if their career plans change more during medical school when compared to men and non-URIM students. Methods Secondary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 69 publications
2
13
0
Order By: Relevance
“…We found that relationships to patients and autonomy were comparatively important to students attracted to general practice which is in line with similar Swiss and international studies [ 19 , 31 ]. Also, in line with results from previous studies, we found a positive association of female sex with attractiveness gynecology/pediatrics [ 27 , 38 ]. In addition, we investigated the association with career in academic or industry sectors and found a strong negative association with female sex.…”
Section: Discussionsupporting
confidence: 93%
“…We found that relationships to patients and autonomy were comparatively important to students attracted to general practice which is in line with similar Swiss and international studies [ 19 , 31 ]. Also, in line with results from previous studies, we found a positive association of female sex with attractiveness gynecology/pediatrics [ 27 , 38 ]. In addition, we investigated the association with career in academic or industry sectors and found a strong negative association with female sex.…”
Section: Discussionsupporting
confidence: 93%
“…To better examine the impact of MS on students' decisions and to expound on previously demonstrated associations 15 we examined these trends again upon graduating from MS. To date, a large portion of available literature focuses on specialty selection and the association with URiM status. Here too, both women and URiM students were more likely, than men and non-URiM students, respectively, to express their intent in working with underserved communities.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to medical specialty choice, the development of an individual physician identity is intrinsically linked with how and where each student envisions their future practice of medicine and can change in concert with career plan reconsiderations. 15 , 16 While any physician regardless of medical specialty type may dedicate their career to the underserved, specific medical specialties are traditionally linked with having a specific focus on providing care in these areas. While these designations are fluid and vary by perspective, historically primary care specialties 17 , 18 and emergency medicine 19–22 have explicitly made this role a part of their professional culture.…”
Section: Introductionmentioning
confidence: 99%
“…First, efforts should be focused on introducing the field of neurosurgery to female medical students at matriculation, when the gender gap in surgical specialty interest is widest. 8 In turn, these efforts may encourage female students who otherwise may not have been interested in neurosurgery to begin exploring the field, thus enabling them to get an early start in developing more competitive applications and dispelling negative notions they may have had about the field. Second, research fellowships and opportunities should be specifically targeted to female neurosurgery residents, as our data show that gender disparities in research productivity widen during residency.…”
Section: Implications Moving Forwardmentioning
confidence: 99%
“…By the end of medical school, female medical students are still less likely than male students to have an interest in surgery or a surgical subspeciality (OR 0.64, 95% CI 0.561-0.727), but by less of a margin. 8 Strategies to address such imbalances and other challenges have been devised and include a focus on mentorship/sponsorship programs and conference scholarships, the establishment of "Women in Surgery" organizations, and awareness efforts regarding burnout. 9 In the absence of multivariable quantitative analyses targeting the early recruitment stage from medical school to residency, the development of an effective plan to bridge gender gaps may prove difficult.…”
mentioning
confidence: 99%